Measurement of IS/IT Investment on the Implementation of ERP and the Effect on company productivity - Qilbaaini Effendi Muftikhali; Apol Pribadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Information technology can not be denied in daily activities and is the source of life of some business processes that cause companies to compete in making IT investments. Noted that IT investment increased significantly. However, the data also indicated this investment is not always followed by the achievement of organizational performance. This is known as IT Productivity Paradox, where the benefits obtained do not match what is invested. This phenomenon has long been discussed to this day. IT Productivity Paradox has become an interesting topic in some circles because some findings find different results. Some research proves that investment in IT / IS has driven the performance of the company, while not at other companies. This study aims to determine the phenomenon of IT productivity. The object of research is an organization that has invested and developed ERP system for the last 2 years. The analysis using Information Economics method. The result of investment measurement from this research shows that the application of ERP using Economic Information method in the period of about 2 years shows total project score (64,6) with predicate of influential project. The total score of the project is derived from three aspects of benefits, namely the real aspect, the quasi-real aspect, and the intangible aspect.